Fungsi dan Peran Elemen Supranatural dalam Folklor Jepang - Jessica Nathania Handayani (Janaru Saja: Jurnal Program Studi Sastra Jepang (Edisi Elektronik), 2020)
This study discusses the role and nature of the supernatural aspects of Japanese folklores. The folklores studied in this research are collected from Japanese folklore internet database and were analyzed using descriptive method. After examining the contents, the result shows that the presence of supernatural aspects in Japanese folklores are to facilitates and implements the functions of folklore itself. They exist in the oral tradition as a medium to the folklore functions; as a projective system, cultural validation, didactic aspect, and lastly, as social control. This demonstrates that the study of folklore can be utilized to explore a group’s historical and sociological elements